2002
DOI: 10.1002/app.10813
|View full text |Cite
|
Sign up to set email alerts
|

Poly(L‐lactide). IX. Hydrolysis in acid media

Abstract: Amorphous and crystallized poly(l-lactide) (PLLA) films are prepared by quenching and annealing at 140°C for 600 min, respectively, from the melt. Their hydrolysis is investigated at pH 2.0 in HCl and dl-lactic acid (DLLA) solutions (37°C) for up to 300 days, and the results are compared with those obtained for PLLA films hydrolyzed at pH 7.4 (phosphate-buffered solution) and pH 12 (NaOH solution). The changes in the weight loss and molecular weight distribution of the PLLA films during hydrolysis in the acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(54 citation statements)
references
References 35 publications
1
50
1
Order By: Relevance
“…The temperature, relative humidity and pH to which the three packages were exposed during the composting conditions are shown in Figure 5a, b. pH is one of the most important factors of hydrolytic polymer degradation, since pH variations can change hydrolysis rates by a few orders of magnitude. [32][33][34][35] In this study, there was a slight alkalization of the pile after the second day of testing, although this difference was not statistically significant at the a = 0.05 level (p = 0.91) during the 30 days of composting.…”
Section: Resultscontrasting
confidence: 62%
“…The temperature, relative humidity and pH to which the three packages were exposed during the composting conditions are shown in Figure 5a, b. pH is one of the most important factors of hydrolytic polymer degradation, since pH variations can change hydrolysis rates by a few orders of magnitude. [32][33][34][35] In this study, there was a slight alkalization of the pile after the second day of testing, although this difference was not statistically significant at the a = 0.05 level (p = 0.91) during the 30 days of composting.…”
Section: Resultscontrasting
confidence: 62%
“…As there were no changes in the sample weights, this suggests that the low molecular weight chains caused by the chain scission are either not water soluble or remain trapped inside the sample. Tsuji concluded that PLA degradation in basic medium is produced by superficial erosion accompanied by a considerable weight loss, while acid or PBS degradation are produced in bulk with very little weight loss [14,16,27].…”
Section: Discussionmentioning
confidence: 99%
“…[7]. Many studies have been carried out on its hydrolytic degradation in different media, including: a neutral solution of buffer phosphate (PBS) at 37 ºC or higher to accelerate degradation [8][9][10][11], an alkaline solution at different temperatures [11][12][13][14][15], an acid solution [16,17] and even studies on enzymatic degradation using enzymes as proteinase K [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The pH of the aqueous medium also affects the degradation reaction rates (Kirby, 1972). Tsuji et al studied the hydrolysis of PLLA films at 37 ºC in alkaline solution (pH 12) acid solution (pH 2.0) (Tsuji and Nakahara, 2001) and phosphate-buffered solutions (pH 7.4) (Tsuji and Ikada, 2000). In the present case, pH can be considered constant.…”
Section: Hydrolytic Damagementioning
confidence: 99%